Effect of family stress on life satisfaction among female workers during the COVID-19 epidemic in China: Exploring the roles of anxiety symptoms and age. (May 2022) - Mei, Songli; Yuan, Tongshuang; Liang, Leilei; Ren, Hui; Hu, Yueyang; Qin, Zeying; Fei, Junsong; Cao, Ruilin; Li, Chuanen; Hu, Yuanchao
The study aimed to investigate the level of life satisfaction (LS) among Chinese female workers after resuming work during the COVID-19 epidemic, and to further explore the potential mediating and moderating roles in the association between family stress and LS. Self-reported questionnaires were completed by 10, 175 participants. Results showed that the level of LS decreased. The family stress had a negative effect on LS, and the effect was mediated by anxiety symptoms. Additionally, age moderated the direct and indirect effects within this relationship. Interventions aiming to improve LS should consider these aspects and younger workers should be given special attention.